Pembelajaran Tari Tradisi Daerah dalam Mengembangkan Kecakapan Budaya dan Kreativitas di Sekolah Menengah: Sebuah Pendekatan Inovatif dalam Pendidikan Multikultural - Eka Pratiwi Estiningtyas; Sri Kusrini; Hesti Susasih (CV Putra Publisher, 2023)
The aim of this research was to investigate ways in which regional traditional dance learning could be used to improve students' cultural skills and creativity in secondary schools. This research investigates how traditional regional dances can be incorporated into the school curriculum with the aim of increasing students' understanding of cultural diversity and increasing creativity. This research found that regional traditional dances help preserve cultural heritage and increase students' multicultural awareness and creative skills. This research method uses qualitative research with a literature review type. Data collection techniques use curriculum document analysis, students become more creative and expressive. The results of this research found that, to support multicultural education and develop 21st century skills among students, regional traditional dances should be more included in the school curriculum.